2022
DOI: 10.1039/d2nr00172a
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the surface chemistry of hard carbon towards high-efficiency sodium ion storage

Abstract: Hard carbon (HC) is the most likely to be commercialized anode material for sodium-ion batteries (SIBs). However, its low initial Coulombic efficiency (ICE) impeding the further large-scale industrialization. Since the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The wide distribution of E ads values at these active sites was also consistent with these results, verifying that the introductions of defects, including edges and vacancies with/without oxygenic functional groups during the ball-milling process can effectively increase active sites for reversible sodium storage, leading to the great improvement on the specific capacity. 21,22,30,67,68…”
Section: Resultsmentioning
confidence: 99%
“…The wide distribution of E ads values at these active sites was also consistent with these results, verifying that the introductions of defects, including edges and vacancies with/without oxygenic functional groups during the ball-milling process can effectively increase active sites for reversible sodium storage, leading to the great improvement on the specific capacity. 21,22,30,67,68…”
Section: Resultsmentioning
confidence: 99%
“…[141,142] Therefore, hard carbons with a low SSA have been widely studied. [143][144][145] Luo et al found that the presence of graphite oxide was able to restrict the foaming of sucrose during its caramelization or dehydration on heating, and the SSA of the prepared hard carbons was limited to only 5.4 m 2 g −1 . [61] This simple modification resulted in an increased ICE from 74% to 83% without sacrificing cycling stability.…”
Section: Nanoporesmentioning
confidence: 99%
“…11 It has been verified that, although SEI films still formed on the surface of graphite in ether-based electrolytes, they were ultrathin with reduced charge-transfer resistance and had no adverse effect on solvent cointercalation. 12,13 Yang et al went further. They verified that not only the ICE but also the specific capacity of rGO could be largely improved by replacing ether-based electrolytes with ester-based electrolytes, benefiting from the advanced SEI film formed in the former.…”
Section: Introductionmentioning
confidence: 99%